2007
DOI: 10.1007/s00467-007-0465-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of clinical and laboratory findings to localize site of urinary infection

Abstract: The aim of this study was to define in children younger than 2 years of age the diagnostic significance of clinical and laboratory findings to localize site of febrile urinary tract infection. We reviewed the records of 185 children younger than 2 years of age admitted to hospital with febrile urinary tract infection. Patients were divided into having either acute pyelonephritis or acute cystitis according to the presence or absence of acute lesions on dimercaptosuccinic acid (DMSA) renal scintigraphy. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 37 publications
(52 reference statements)
6
26
0
13
Order By: Relevance
“…The frequency of acute renal changes was higher in the upper poles of the kidneys. These findings were in agreement with the results as reported in the literature [22][23][24]. Peripheral cortical defects were not associated with any loss of volume, in comparison to some authors' results that showed lesions with scintigraphic presentation suggesting scars [19].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The frequency of acute renal changes was higher in the upper poles of the kidneys. These findings were in agreement with the results as reported in the literature [22][23][24]. Peripheral cortical defects were not associated with any loss of volume, in comparison to some authors' results that showed lesions with scintigraphic presentation suggesting scars [19].…”
Section: Discussionsupporting
confidence: 95%
“…Abnormal initial DMSA scan in our study could help to detect infected kidneys at risk of subsequent scarring and those children who are at risk of future complications [20,24]. The early definition of such a high-risk group may be of interest, particularly in distant geographical areas in our country, where compliance with treatment and follow-up may be low.…”
Section: Discussionmentioning
confidence: 87%
“…Según los estudios, el valor de PCR es significativamente más alto al momento del ingreso cuando se detecta daño renal por gammagrafía con DMSA tras una pielonefritis. [21][22][23][24] Del mismo modo, en este estudio, se detectó mayor nefroesclerosis en los pacientes con valores positivos de PCR, y se halló una diferencia estadísticamente significativa entre estos pacientes y aquellos con valores negativos de PCR (p < 0,0001).…”
Section: Discussionunclassified
“…However, some studies have shown that fever is not enough for the diagnosis of pyelonephritis, as a sole indicator 9,11 .…”
Section: Discussionmentioning
confidence: 99%